Cottesloe 50 years later: Did the Dutch Reformed Church answer to the call? - Van der Merwe, JM (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The Cottesloe consultation took place fifty years ago. The declaration after the consultation made a call to the church in South Africa to get involved in the struggle against the unjust system of Apartheid. Although the declaration was met by negative reaction from the Dutch Reformed Church, the church struggled since 1961 through various synods to answer to the call of Cottesloe. After the first answer, Human relations and the South African scene in light of scripture, was rejected, it was back to the drawing board. The final answer was eventually given at the Rustenburg conference in 1990 after several important impulses influenced the theological thinking in the church. Although the Dutch Reformed Church officially answered to the call in 1990 the challenge of Cottesloe still remains, fifty years later.